2016
DOI: 10.1371/journal.pgen.1006149
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Multiple Loci Influencing Normal Human Facial Morphology

Abstract: Numerous lines of evidence point to a genetic basis for facial morphology in humans, yet little is known about how specific genetic variants relate to the phenotypic expression of many common facial features. We conducted genome-wide association meta-analyses of 20 quantitative facial measurements derived from the 3D surface images of 3118 healthy individuals of European ancestry belonging to two US cohorts. Analyses were performed on just under one million genotyped SNPs (Illumina OmniExpress+Exome v1.2 array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
180
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(193 citation statements)
references
References 64 publications
9
180
0
4
Order By: Relevance
“…In contrast to a recent GWAS on human body height 41 , which, due to the widespread availability of the phenotype, was able to identify 423 loci in combined samples over two orders of magnitude larger than what was used here, the specialized phenotype data needed for investigating 3D facial shape is limited to a few, smaller cohorts. Using the PITT cohort from Shaffer et al 6 , we managed to substantially increase the number of loci identified. In fact, these results are unmatched by any imaging-based facial GWAS to date.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a recent GWAS on human body height 41 , which, due to the widespread availability of the phenotype, was able to identify 423 loci in combined samples over two orders of magnitude larger than what was used here, the specialized phenotype data needed for investigating 3D facial shape is limited to a few, smaller cohorts. Using the PITT cohort from Shaffer et al 6 , we managed to substantially increase the number of loci identified. In fact, these results are unmatched by any imaging-based facial GWAS to date.…”
Section: Discussionmentioning
confidence: 99%
“…Shaffer et al conducted a GWAS analyzing 20 quantitative facial measurements on 3D images of a cohort of about 3100 American individuals of European descent. They found six regions associated with variable facial traits, in which several genes are located which are known to be associated with craniofacial development: MAFB, PAX9, MIPOL1, ALX3, HDAC8, and PAX1 [56]. Furthermore, they were able to replicate the correlation between nasal ala length and SNPs in CACNA2D3 and PRDM16 and between intercanthal width and SNP rs7559271 in PAX3 .…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…Generally, it is helpful to control for other factors that might influence an association or the involved variables (Cohen et al, 2003). With respect to testosterone and fWHR, this could include age, body-mass index, genetic influences, and physical health and exercise (e.g., Zitzmann and Nieschlag, 2001; Hehman et al, 2014; Geniole et al, 2015; Shaffer et al, 2016). Therefore, the authors' analysis should include an age covariate, since it is critical to account for strong developmental effects on the variables of interest.…”
mentioning
confidence: 99%